On the Representativeness of Constitutional Courts: How to Strengthen the Legitimacy of Rights Adjudicating Courts without Undermining Their Independence - Mattias Kumm (Judicial Power: How Constitutional Courts Affect Political Transformations, 2019)
Constitutional courts, like legislatures, are representative institutions. But in virtue of what are they representative and what are the variables that might raise their level of representativeness, without unduly undermining the impartiality and independence that is required for courts to successfully play this role? The chapter distinguishes between four complementary dimensions of representativeness: volitional, identitarian, argumentative, and vicarious. I argue that it is not desirable to increase courts' volitional representativeness (strengthening the electoral link between judges and the people). Even though identitarian representativeness is important in contexts of historical practices of exclusion, the focus of constitutional designers should not be limited to these factors. Other normatively salient variables that should be the focus of constitutional designers include argumentative representativeness, implicating questions of methodology, and style and structure of judicial opinions. Furthermore, vicarious representativeness, which concerns the constitutional embeddedness of judicial institutions in the political system and, more specifically, the mechanisms that allow political branches to challenge decisions of courts should be among the factors on which attention is focused.
Keywords: 300